Comparative study of hydrogen storage on metal doped mesoporous materials - Carraro, Paola María (2018)
The hydrogen adsorption capacity of mesoporous materials MCM-41 modified with Co, Fe, Ti, Mg and Ni at 77 K and 10 bar was investigated. Various techniques including XRD, N2 adsorption and DRUV–vis were employed for the materials characterization. The results showed that a low nickel loading on MCM-41 support promoted the presence of hydrogen-favorable sites, increasing the hydrogen storage capacity.